ATIVIDADE ENZIMÁTICA EM PLÂNTULAS DE Eucalyptus grandis PROVENIENTES DE SEMENTES ENVELHECIDAS ARTIFICIALMENTE E NATURALMENTE1 - Camargo, Maria Letícia Pereira De [UNESP]; Mori, Edson Seizo [UNESP]; Mello, Eduardo José De; Oda, Shinitiro; Lima, Giuseppina Pacce [UNESP] (Universidade Federal de Santa Maria, 2000)
This research studied the standard procedure developed for crop seeds to examine the biochemical processes in accelerated aging seeds (kept for 96 hours at 42ºC and 100% RH) and stored seeds (from 5, 10 and 15 years) using isoenzyme electrophoresis and peroxidase activity by colorimetric assay. There was significant decrease (z-test) in the vigor of accelerated aging seeds (54,9%) when compared to the stored ones (97,25%, 95,22% and 89,25%).The peroxidase (PER, EC 1.11.1.7) activity was low, however there was na increase in activity with seed aging. There was a simultaneous increase in both malate dehidrogenase (MDH, EC 1.1.1.37) and esterase (EST, EC 3.1.1.1) activities. The results fllowed the in crease in the seeds storage period of time and of the stress which occurs due to the temperature and humidity conditions utilized in accelerated aging.

O presente estudo empregou o procedimento de envelhecimento artificial, submetendo sementes por 96 horas à 42° C e 100% de UR para compará-las com sementes estocadas por 5, 10 e 15 anos e utilizou eletroforese de isoenzimas e atividade de peroxidase por método colorimétrico. Houve um decréscimo significante na germinação das sementes envelhecidas artificialmente, quando comparadas com as sementes estocadas. A atividade da peroxidase foi baixa, porém houve uma curva ascendente que acompanhou a idade das sementes. Observou-se um aumento nas atividades da malato desidrogenase e α-esterase 2 e 3 e uma diminuição acentuada para α-esterase 1 e baixa para a fosfatase ácida. Os resultados acompanharam o aumento do tempo de estocagem das sementes e do estresse que ocorre por causa das condições de temperatura e umidade empregadas no processo de envelhecimento artificial.
ENZYME ACTIVITIES FROM ACCELERATED AGING AND STORAGED SEEDS OF Eucalyptus grandis
Keywords: accelerated aging; seeds; Eucalyptus grandis; enzyme activities; envelhecimento; sementes; Eucalyptus grandis; atividade enzimática